European Society of Coloproctology Colorectal Robotic Surgery Training for the Trainers Course – the first pilot experience - Eardley, N. J.; Matzel, K. E.; Gómez Ruiz, M.; Khan, J. S.; Riley, S. A.; Donnelly, M. T.; Tou, S. (Colorectal Disease, 2020)
Aim: Currently, there is no established colorectal specific robotic surgery Train the Trainer (TTT) course. The aim was to develop and evaluate such a course which can then be further developed to be incorporated within the planned European Society of Coloproctology (ESCP)/European School of Coloproctology (ESC) robotic colorectal surgery training curriculum. Method: After identifying the need for such a course within a training programme, the course was developed by a subgroup of the ESCP/ESC. A scoping literature review was performed and the content and materials for the course were developed by a team consisting of two gastroenterologists with a combined experience of 30 years of facilitating TTT courses, a robotic surgeon and proctor with laparoscopic TTT faculty experience and experienced robotic and laparoscopic colorectal trainers. The course was evaluated by asking delegates to complete pre- and post-course questionnaires. Results: There were eight delegates on the course from across Europe. Delegates increased their knowledge of each of the course learning objectives and identified learning points in order to change practice. The feedback from the delegates of the course was positive across several areas and all felt that they had achieved their own personal objectives in attending the course. Conclusion: This pilot robotic colorectal TTT course has achieved its aim and demonstrated many positives. There is a need for such a course and the evaluation processes have provided opportunities for reflection, which will allow the development/tailoring of future robotic colorectal TTT courses to help develop robotic training further.
CRIS-Team Scopus Importer:2020-08-21
Keywords: colon; rectum; robotic surgical procedure; robotics; surgery; training